2021
DOI: 10.3389/fnhum.2021.662204
|View full text |Cite
|
Sign up to set email alerts
|

Stuttering: A Disorder of Energy Supply to Neurons?

Abstract: Stuttering is a disorder characterized by intermittent loss of volitional control of speech movements. This hypothesis and theory article focuses on the proposal that stuttering may be related to an impairment of the energy supply to neurons. Findings from electroencephalography (EEG), brain imaging, genetics, and biochemistry are reviewed: (1) Analyses of the EEG spectra at rest have repeatedly reported reduced power in the beta band, which is compatible with indications of reduced metabolism. (2) Studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 139 publications
(256 reference statements)
4
11
0
Order By: Relevance
“…Next, we demonstrate that auditory stimulation is resulting in a speech quality improvement. The effectiveness of β -range BB stimulation to improve speech quality in AWS agrees with earlier studies suggesting a link between β deficit and stuttering 6,25,41 . Moreover, our results suggest that there is a dose-effect relation of speech improvement on the increase of β power in speech centers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Next, we demonstrate that auditory stimulation is resulting in a speech quality improvement. The effectiveness of β -range BB stimulation to improve speech quality in AWS agrees with earlier studies suggesting a link between β deficit and stuttering 6,25,41 . Moreover, our results suggest that there is a dose-effect relation of speech improvement on the increase of β power in speech centers.…”
Section: Discussionsupporting
confidence: 89%
“…Neurophysiology studies have offered a promise of actionable discoveries in stuttering causes. A number of studies showed that the activity in the EEG β spectrum range (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), which is commonly heightened in awake state and focused activities 4 , is reduced in individuals with stuttering (reviewed in 5 ). EEG and magnetoencephalographic (MEG) studies have shown that in adults who stutter (AWS), as compared to the control group, α power is higher 5,6 while β power is lower during speech production 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Alm proposed that reduced beta power at rest in AWS could be an indicator of limited neuronal supply that, through a direct effect, may result in stuttering by the reduction of neuronal firing frequency in the motor speech system. 10 In our opinion, the increased alpha and beta power over motor areas through SP for dysfluent utterances is arduous to explain with the hypothesis of neuronal firing deficiency. Moreover, increased delta band frequency has been associated with fluency, whereas in decreased metabolic rate, low band frequencies are empowered.…”
Section: Discussionmentioning
confidence: 94%
“…He proposed 2 ways in which a reduced supply of energy results in stuttering. 10 In direct effect theory, stuttering is caused by a reduced rate of firing by energy-deprived neurons involved in speech production. Moreover, he suggested an indirect effect hypothesis wherein metabolic impairments cause an elevated tonic level of synaptic dopamine, which, in turn, results in stuttering.…”
Section: Introductionmentioning
confidence: 99%